Filantropi Islam di Minangkabau: Membentuk Solidaritas Sosial Melalui Adat dan Agama - Deni Putra, Muhammad; Fadilla, Siti; Budia Warman, Arifki; Aliman Shahmi, Mohammad; Mansur, Muhammad (Indonesian Journal of Islamic Economics and Business, 2024)
This research focuses on Islamic philanthropy in Minangkabau and its contribution to building social solidarity through the integration of local customs and religion. The method used is a literature review, collecting data from relevant articles, books, and case studies. The purpose of this study is to explore how Minangkabau traditional values, such as "gotong royong" (mutual cooperation) and "badunsanak" (kinship solidarity), play a role in facilitating philanthropic practices. The findings indicate that these local traditions, combined with Islamic teachings, strengthen social bonds and enhance community welfare. Furthermore, the role of women in managing family resources and the contributions of organizations like Muhammadiyah and Nahdlatul Ulama help reinforce structured philanthropic practices. Education in Islamic boarding schools (pesantren) also plays a crucial role in instilling philanthropic values in the younger generation. In conclusion, Islamic philanthropy based on local customs in Minangkabau not only strengthens social solidarity but also contributes to poverty alleviation and community well-being.